The Impact of Integrating Organizational Culture and Governance Mechanisms on the Quality of Accounting Disclosure of Intellectual Capital: An Applied Study (Al-Farooq Journal of Sciences, 2026)
This study aimed to identify the impact of integrating organizational culture and governance mechanisms on improving the quality of accounting disclosure of intellectual capital. Accordingly, this study seeks to analyze and measure the impact of integrating organizational culture and governance mechanisms on the quality of accounting disclosure of intellectual capital. This is achieved through an applied study targeting a group of organizations, with the goal of obtaining results that contribute to developing accounting and control practices and providing recommendations that support decision-makers in enhancing transparency and achieving optimal use of intellectual resources within organizations. Intellectual capital within organizations is of paramount importance in light of the increasing trend towards a knowledge-based economy and the growing reliance on intangible assets as a primary source for achieving competitive advantage and sustainability. The study stems from the importance of intellectual capital as one of the most important strategic resources that contribute to creating value and improving institutional performance, and the consequent need to provide high-quality accounting information that reflects the reality of these resources and supports the needs of financial report users. The study adopted a descriptive-analytical approach. Data was collected through a questionnaire distributed to a sample of managers, accountants, auditors, audit committee members, and employees in the financial and control departments of several institutions under study. A range of appropriate statistical methods were employed to analyze the data and test the study's hypotheses, including Cronbach's alpha, descriptive statistics, correlation analysis, and regression analysis.The study concluded that organizational culture has a positive and significant impact on the quality of accounting disclosure regarding intellectual capital. The results also demonstrated a positive impact of governance mechanisms—namely, the board of directors, audit committees, internal audit, transparency, and disclosure—on the quality of accounting information related to intellectual capital. Furthermore, the findings indicated that the integration of organizational culture and governance mechanisms contributes more significantly to enhancing the quality of disclosure than either factor alone. This underscores the importance of adopting an organizational environment that supports transparency and accountability, alongside the effective application of governance principles. The study recommended fostering an organizational culture based on integrity, transparency, and participation, and developing governance mechanisms within institutions to support the disclosure of intellectual capital components. It also recommended encouraging regulatory and professional bodies to issue clearer guidelines and standards for disclosing intellectual assets, thereby contributing to improved financial reporting quality and increased investor and stakeholder confidence.
Keywords: Organizational culture, corporate governance, quality of accounting disclosure, intellectual capital, transparency, financial reporting, competitive advantage.